Possibilities of Simultaneous In-Cylinder Reduction of Soot and NOx Emissions for Diesel Engines with Direct Injection. (28th October 2008) - Wagner, U.; Eckert, P.; Spicher, U.
Abstract : Up to now, diesel engines with direct fuel injection are the propulsion systems with the highest efficiency for mobile applications. Future targets in reducingCO 2 -emissions with regard to global warming effects can be met with the help of these engines. A major disadvantage of diesel engines is the high soot and nitrogen oxide emissions which cannot be reduced completely with only engine measures today. The present paper describes two different possibilities for the simultaneous in-cylinder reduction of soot and nitrogen oxide emissions. One possibility is the optimization of the injection process with a new injection strategy the other one is the use of water diesel emulsions with the conventional injection system. The new injection strategy for this experimental part of the study overcomes the problem of increased soot emissions with pilot injection by separating the injections spatially and therefore on the one hand reduces the soot formation during the early stages of the combustion and on the other hand increases the soot oxidation later during the combustion. Another method to reduce the emissions is the introduction of water into the combustion chamber. Emulsions of water and fuel offer the potential to simultaneously reduceNO x and soot emissions while maintaining a high-thermal efficiency. This article presents a theoretical investigation of the use of fuel-water emulsions in DI-Diesel engines. The numerical simulations are carried out with the 3D-CFD code KIVA3V. The use of different water diesel emulsions is investigated and assessed with the numerical model.